Cardiac Amyloidosis: Evolving Diagnosis and Management: A Scientific Statement From the American Heart Association - Kittleson, Michelle M; Maurer, Mathew S; Ambardekar, Amrut V; Bullock-Palmer, Renee P; Chang, Patricia P; Eisen, Howard J; Nair, Ajith P; Nativi-Nicolau, Jose; Ruberg, Frederick L (Circulation (New York, N.Y.), 2020)
Transthyretin amyloid cardiomyopathy (ATTR-CM) results in a restrictive cardiomyopathy caused by extracellular deposition of transthyretin, normally involved in the transportation of the hormone thyroxine and retinol-binding protein, in the myocardium. Enthusiasm about ATTR-CM has grown as a result of 3 simultaneous areas of advancement: Imaging techniques allow accurate noninvasive diagnosis of ATTR-CM without the need for confirmatory endomyocardial biopsies; observational studies indicate that the diagnosis of ATTR-CM may be underrecognized in a significant proportion of patients with heart failure; and on the basis of elucidation of the mechanisms of amyloid formation, therapies are now approved for treatment of ATTR-CM. Because therapy for ATTR-CM may be most effective when administered before significant cardiac dysfunction, early identification of affected individuals with readily available noninvasive tests is essential. This scientific statement is intended to guide clinical practice and to facilitate management conformity by covering current diagnostic and treatment strategies, as well as unmet needs and areas of active investigation in ATTR-CM.